From timeless Japanese wood joinery to advanced ceramic joint interlocking - Patrizia Hoffmann; Larissa Wahl; Swantje Funk; Tobias Fey (Discover Materials)
Abstract Efficiency and adaptability are key factors in the development of high-performance architectural hybrid materials. While monolithic ceramics have limitations in advanced applications, hybrid structures combining multiple components or geometries offer enhanced adaptability and functionality. This study explores modular, interlocking ceramic structures with inherent stability, consisting of detachable and individually replaceable building blocks. Inspired by timeless Japanese Wood Joining (WJ), we have transitioned from the traditional bonded wood joints to advanced interlocking rigid joints without additional bonding phases to meet the requirements of self-supporting ceramic structures under demanding conditions such as high temperatures. To address the brittle nature of ceramics, we additionally incorporated the principles of Topological Interlocking (TI), which localizes fracture propagation and prevents catastrophic failure using modularity, providing a significant advantage over monolithic structures. We present a novel hybrid approach, referred to as Ceramic Joint Interlocking (CJI), which combines the self-supporting stability of WJ with the modularity of TI. Using low-pressure ceramic injection molding, we fabricated intricate interlocking ceramic components with multiple integrated interlocking joints that assemble without external forces. Mechanical performance was evaluated using deflection measurements, which highlight their potential for structural integrity and adaptability. This novel approach opens the way for modular, reusable, and inherently stable ceramic structures, increasing the potential for high-performance applications that require durability and flexibility.